An experimental method for characterizing unsaturated 1D flow in tubular braided preforms during bladder‐assisted resin transfer molding. Issue 12 (16th September 2017) - Schillfahrt, Christian; Fauster, Ewald; Schledjewski, Ralf
Abstract : The work presented in this paper addresses the development of an efficient approach to investigate the unsaturated in‐plane impregnation behavior of tubular braided reinforcement materials in a bladder‐assisted resin transfer molding process. The basic idea is to record the macroscopic flow front advancement during a pressure‐driven injection of a test fluid by using a transparent monolithic mold and optical measurement methods. The experimental setup further comprises sophisticated process control to accomplish a fully automated and highly repeatable test procedure. As the filling behavior of the braided fabrics predominantly shows unidirectional characteristics, the so‐called unsaturated apparent permeability of these textile reinforcements can be determined, which can be used as an input parameter in one‐dimensional flow simulations. A verification of the test setup is accomplished by means of saturation measurements on different braided preforms, which are compared with predicted flow front profiles. POLYM. COMPOS., 39:4666–4677, 2018. © 2017 Society of Plastics Engineers